ENHANCING FUTURE ENGINEERS’ PROFESSIONAL SKILLS THROUGH COLLABORATIVE LEARNING (International Educators Conference, 2025)
In a landscape where engineering tasks increasingly demand teamwork, effective communication, and interdisciplinary collaboration, traditional lecture‐centered instruction may fail to fully prepare graduates for professional challenges. Collaborative learning, as an educational approach, immerses students in group interactions that mirror the dynamics of engineering teams. By engaging in shared problem solving, peer feedback, and collective reflection, future engineers develop critical professional skills such as communication, leadership, and adaptability. This article examines how integrating collaborative learning into engineering curricula bridges the gap between theoretical knowledge and real‐world practice, fostering competence and confidence in graduates poised to enter complex work environments.